2015
DOI: 10.1097/md.0000000000001595
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Modified Posterior Operation to Treat Kümmell's Disease

Abstract: The present study aimed at examining the curative effect of modified posterior operation on treatment of Kümmell's disease.About 30 patients of Kümmell's disease with complete image and clinical data treated during June 2004 to July 2013 were conducted with anterior and posterior approaches, respectively. Kyphotic Cobb angle, fractured vertebra wedge angle, and the anterior and posterior heights of fractured vertebra were all measured through x-ray before and after operation, and the pain visual analog scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Kashii et al 12 also reported no significant differences between the two operations in the estimated mean blood loss and mean duration of surgery. However, Wang et al 11 reported overtly longer operation time and slightly increased blood loss in AR compared with PO ( Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Kashii et al 12 also reported no significant differences between the two operations in the estimated mean blood loss and mean duration of surgery. However, Wang et al 11 reported overtly longer operation time and slightly increased blood loss in AR compared with PO ( Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…Only 3 cohort trials 11 , 12 , 13 compared AR and PO for clinical and radiological data. These studies all found no significant differences between the two procedures with respect to pain relief, neurological and function improvement ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of these studies focusing on surgical outcomes for OVF with neurological deficits were reported from Japan, a country with the most advanced aging society in the world. There are several studies from other countries such as China, France or Korea; however, the number of patients in their samples were small and studies with a large number of patients is limited [15][16][17] . There is one previous, large-scale, systematic review that included 596 OVF patients with delayed neurological deficit from 29 publications 9) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intervertebral cleft can heal through the bone graft. Wang et al [ 15 ] adopted transpedicular vertebral body grafting combined with vertebral pedicle screw fixation to treat patients with Kümmell disease. Compared with the traditional anterior approach, this modified posterior operation offers equivalent effects on pain relief, kyphosis correction, and improvements in neurological function.…”
Section: Discussionmentioning
confidence: 99%